Synthesis of new carbon material produced from human hair and its evaluation as electrochemical supercapacitor. Issue 19 (1st October 2020) - Bal Altuntaş, Derya; Aslan, Sema; Akyol, Yeşim; Nevruzoğlu, Vagif
ABSTRACT: In this study, carbon material similar to graphene structure (GLS) was prepared from graphite and the carbonization of Turkish human hair fibers (HHC) and utilized for the modification of electrode to evaluate the supercapacitance performance. Electrochemical characterization of the HHC-based GLS (HHC-GLS) modified electrodes have been carried out with cyclic voltammetry and electrochemical impedance spectroscopy. The morphology and chemical composition of the resultant GLSs were characterized by scanning electron microscopy, X-Ray diffraction spectroscopy, Raman and Fourier Transform infrared spectroscopy analysis. HHC-GLS displayed a good electrochemical activity than the graphite sourced graphene and possess very similar morphological properties with commercial graphene. Carbonization of the waste hair was carried out at 280°C to improve the pore structure as the first step of GLS synthesis. HHC-GLS modified electrode exhibited the best electrochemical activity and utilized as a charge storage device. The best specific capacitance value was found to be 139.00 F g −1 in 6.00 M KOH(aq) at a scan rate of 100.00 mV s −1 and good stability over 500 cycles. Whereas an energy density of 19.3 Wh kg −1 and power density of 6.95 kW kg −1 were obtained from the electrode when operated in the voltage range from −1.00 to 0.00 V. This work offers a new approach to human hair waste management in terms of promising green energy applications. This study was patented by the Turkish Patent and Trademark Office (Turkish Patent Institute Application Number: (2019/22841)).